2020
DOI: 10.1186/s12984-020-00789-w
|View full text |Cite
|
Sign up to set email alerts
|

Development of the Home based Virtual Rehabilitation System (HoVRS) to remotely deliver an intense and customized upper extremity training

Abstract: Background After stroke, sustained hand rehabilitation training is required for continuous improvement and maintenance of distal function. Methods In this paper, we present a system designed and implemented in our lab: the Home based Virtual Rehabilitation System (HoVRS). Fifteen subjects with chronic stroke were recruited to test the feasibility of the system as well as to refine the design and training protocol to prepare for a future efficacy study. HoVRS was placed in subjects’ homes, and subjects were as… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
66
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(67 citation statements)
references
References 30 publications
1
66
0
Order By: Relevance
“…Our group's study of home based rehabilitation in persons with chronic stroke has demonstrated some interesting new trends. Adherence rates with these subjects has been comparable to other studies of technology supported, home based rehabilitation and better than traditional home based exercise programs in persons with stroke ( 64 , 65 ). Interestingly, age and previous computer experience did not have an impact on adherence ( 76 ), similar to findings of a recent home based rehabilitation study ( 77 ).…”
Section: Comparing Home and Facility Based Rehabilitationsupporting
confidence: 68%
See 2 more Smart Citations
“…Our group's study of home based rehabilitation in persons with chronic stroke has demonstrated some interesting new trends. Adherence rates with these subjects has been comparable to other studies of technology supported, home based rehabilitation and better than traditional home based exercise programs in persons with stroke ( 64 , 65 ). Interestingly, age and previous computer experience did not have an impact on adherence ( 76 ), similar to findings of a recent home based rehabilitation study ( 77 ).…”
Section: Comparing Home and Facility Based Rehabilitationsupporting
confidence: 68%
“…The camera-based system collects finger and arm position at a fidelity and speed that allows HoVRS to utilize real time algorithms to shape desired movement patterns. This high quality data also allows the system to provide kinematic data to therapists on or offline, allowing them to monitor and modify ‘patients’ rehabilitation programs remotely ( 64 ). Recent pilot study subjects demonstrated statistically and clinically significant improvements in hand motor performance as measured by clinical tests [mean UEMA improvement = 4.53 (SD = 2.3), Repeated Measures ANOVA ( p < 0.001)] ( 65 ).…”
Section: Home Based Rehabilitationmentioning
confidence: 99%
See 1 more Smart Citation
“…Block et al [ 10 ] designed a single-finger exoskeleton training device based on three-dimensional (3D) printing technology, but it shows some disadvantages such as poor flexibility and high cost. Qiu et al [ 11 ] optimized the finger joint rehabilitation training device and initially realized remote rehabilitation, but it still showed the shortcomings of single system control and unstable performance, which has to be optimized further.…”
Section: Introductionmentioning
confidence: 99%
“…A similar system architecture was used by Adamovitch et al in a virtual reality-based exercise system for hand rehabilitation in which a web portal was set up for patient-database remote access, while patients used a VR-based application set up on a PC computer [ 10 ]. A current version of the system, described by Qiu et al, uses a LeapMotion controller with a series of games with real-time feedback by a virtual therapist while a remote web portal is set up for the clinicians and scientists to collect the data, guide patients, and select adequate exercises [ 28 ]. Authors reported high adherence to the training regime and improved patient scores in Fugl–Meyer assessment.…”
Section: Discussionmentioning
confidence: 99%